Persistent fetal infection with bovine viral diarrhea virus differentially affects maternal blood cell signal transduction pathways - Smirnova, Natalia P. (American Physiological Society, 2009)
The consequences of viral infection during pregnancy include impact on fetal and maternal immune responses and on fetal development. Transplacental infection in cattle with noncytopathic bovine viral diarrhea virus (ncpBVDV) during early gestation results in persistently infected (PI) fetuses with life-long viremia and susceptibility to infections. Infection of the fetus during the third trimester or after birth leads to a transient infection cleared by a competent immune system. We hypothesized that ncpBVDV infection and presence of an infected fetus would alter immune response and lead to downregulation of proinflammatory processes in pregnant dams. Naïve pregnant heifers were challenged with ncpBVDV2 on day 75 (PI fetus) and day 175 [transiently infected (TI) fetus] or kept uninfected (healthy control fetus). Maternal blood samples were collected up to day 190 of gestation. Genome-wide microarray analysis of gene expression in maternal peripheral white blood cells, performed on days 160 and 190 of gestation, revealed multiple signal transduction pathways affected by ncpBVDV infection. Acute infection and presence of a TI fetus caused upregulation of the type I interferon (IFN) pathway genes, including dsRNA sensors and IFN-stimulated genes. The presence of a PI fetus caused prolonged downregulation of chemokine receptor 4 (CXCR4) and T cell receptor (TCR) signaling in maternal blood cells. We conclude that: 1) infection with ncpBVDV induces a vigorous type I IFN response, and 2) presence of a PI fetus causes downregulation of important signaling pathways in the blood of the dam, which could have deleterious consequences on fetal development and the immune response.